K–Ar isochron age and paleomagnetism of diabase along the trans-Avalon aeromagnetic lineament—evidence of Late Triassic rifting in Newfoundland - Hodych, J. P.; Hayatsu, A. (Canadian Journal of Earth Sciences, 1980)
A prominent aeromagnetic lineament crosses the Avalon Peninsula of Newfoundland from 46°50.4′N, 53°45.9′W to 47°22.1′N, 52°30.0′W. It is shown to be at least partly caused by diabase dikes of Late Triassic and possibly Early Jurassic age which are probably related to the Shelburne diabase dike and the North Mountain basalt, both of Nova Scotia. All are thought to have resulted from rifting which preceded opening of the Atlantic.Unmetamorphosed diabase was found at three sites along the trans-Avalon aeromagnetic lineament: as narrow sills at site 1 (46°58.0′N, 53°25.4′W), as a narrow dike at site 2 (47°4.7′N, 53°7.6′W), and as large angular boulders at site 3 (47°11.0′N, 52°52.2′W).For sites 1 and 2, analyses of seven diabase samples fall on a single K–Ar isochron whose intercept on the 40 Ar/ 36 Ar axis is at 215 ± 45 and whose slope gives a Late Triassic age of 201.1 ± 2.6 Ma. Analyses of two diabase samples from the Shelburne dike fall close to this isochron suggesting a similar age. Paleomagnetism adds support; the virtual paleopole measured for sites 1 and 2, using 12 oriented diabase samples demagnetized in 300 Oe (23 880 A/m) alternating field (AF), falls at 87.8°E, 72.9°N (dp = 3.0°, dm = 4.3°), close to the virtual paleopole reported for the Shelburne dike.For site 3, analyses of two samples fall on the K–Ar isochron reported for the North Mountain basalt, tentatively suggesting that the intrusion at site 3 occurred about 10 Ma later than at sites 1and 2.